Awareness and knowledge on eye donation among university students - Bharti, M.K.; Reddy, S.C.; Tajunisah, I.; Ali, N.A.M. (Malaysian Medical Association, 2009)
Four hundred (400) students studying first year Medicine, Dentistry, Laboratory Technology, Pharmacy, Biomedicine and Bioengineering degree courses in the University of Malaya were assessed on their awareness and knowledge on eye donation using an open ended questionnaire. The majority of the students (344, 86%) in this study were aware about eye donation; the awareness was higher in biomedical (77.1%) and medical students (76.7%) compared to the others (55.9% - 70.7%). One hundred and eight students (27%) were willing to donate their eyes. Most of the students (376, 94%) did not know about any eye bank in Malaysia. One hundred and sixty (40%) students were aware that whole eye can be removed from the donor and 101 (25.25%) were aware that the cornea can be removed separately. However, only 121 (30.25%) knew that donated eyes were used for corneal grafting. More than half of the students (231, 57.7%) did not know that the donor eye could be stored before transplantation. The results of this study indicate that there is a need to educate the young adults in our society about corneal transplantation so that they can in turn motivate other members of society and their own family members to become eye donors, thus facilitating the availability of donor corneas for corneal transplantation in Malaysia.